Advancing Public Service Quality through Indonesia’s Electronic-Based Government System - Sundari, Wildan; Sartika, Ika (Sean Institute, 2025)
Indonesia's Electronic-Based Government System (SPBE) has emerged as a transformative framework for enhancing public service quality through digital governance. This study examines SPBE's role in improving efficiency, transparency, and accessibility by analyzing its implementation across four domains: governance, management, services, and infrastructure. Despite progress reflected in Indonesia's improved SPBE Index (3.12 in 2024) and global e-government rankings, challenges such as the digital divide (2,881 villages lack internet access), low civil servant digital literacy (30%), cybersecurity threats (400 million attacks in 2023), and system fragmentation (24,000 unintegrated applications) hinder optimal outcomes. The research employs a literature review and bibliometric analysis of 533 studies, identifying six thematic clusters that highlight SPBE's structural foundations, service quality impacts, and regional disparities. Findings reveal that while SPBE streamlines workflows through unified portals like the Public Service Portal, inconsistencies in infrastructure maintenance, user interface design, and cross-agency integration persist. The SERVQUAL model (Zeithaml et al., 1985) underscores gaps in reliability, responsiveness, and empathy, particularly for rural and digitally excluded populations. Policy recommendations include targeted infrastructure development, tiered digital training programs, security-by-design adoption, and centralized data governance to address fragmentation. The study concludes that SPBE's success depends on bridging implementation gaps through institutional reinforcement, equitable resource distribution, and continuous evaluation, positioning it as a catalyst for Indonesia's bureaucratic reform and inclusive digital transformation.